Molecular identification of iridoviruses infecting various sturgeon species in Europe. Issue 1 (19th May 2016) - Bigarré, L; Lesne, M; Lautraite, A; Chesneau, V; Leroux, A; Jamin, M; Boitard, P M; Toffan, A; Prearo, M; Labrut, S; Daniel, P
Abstract: Iridoviridae are known to cause disease in sturgeons in North America. Here, histological and molecular methods were used to screen for this family of virus in sturgeons from various European farms with low‐to‐high morbidity. Some histological samples revealed basophilic cells in the gill and labial epithelia, strongly suggesting the accumulation of iridovirus particles. Newly developed generic PCR tests targeting the major capsid protein (MCP) gene of sturgeon iridoviruses identified in North America, namely the white sturgeon iridovirus and the Namao virus (NV), produced positive signals in most samples from four sturgeon species: Russian ( Acipenser gueldenstaedtii ), Siberian ( A. baerii ), Adriatic ( A. naccarii ) and beluga ( Huso huso ). The sequences of the PCR products were generally highly similar one another, with nucleotide identities greater than 98%. They were also related to (74–88%), although distinct from, American sturgeon iridoviruses. These European viruses were thus considered variants of a single new virus, provisionally named Acipenser iridovirus‐European (AcIV‐E). Moreover, three samples infected with AcIV‐E showed genetic heterogeneity, with the co‐existence of two sequences differing by five nucleotides. One of our European samples carried a virus distinct from AcIV‐E, but closely related to NV identified in Canada (95%). This study demonstrates the presence of two distinct sturgeon iridoviruses in Europe: a new genotype AcIV‐E and an NV‐related virus.